Determinación de metales pesados en plantas en áreas explotadas por la minería aurífera en el sector de Nambija-Zamora Chinchipe-Ecuador - Quezada Rivera, Henry Vinicio (2014)
This work was conducted in Sector Nambija of Zamora Chinchipe, between the months of June to August 2013. The aim of this study was to determine the contamination by heavy industry plants in native metals, through the determination of absorbed amounts of such metals and assessing their potential for restoration of degraded habitats. Values of mercury, cadmium, lead, arsenic, iron and copper found in leaves, roots and stems of plants taken from abandoned gold mining areas in the montane cloud forest are presented. The heavy metal content was determined by atomic absorption spectrophotometry. Resulting in species of the family Poaceae (Cortaderia jubata), Melastomataceae (Monochatum lineatum), Asteraceae (Erato polymniopdes and Ageratina pichichensis) and Onagraceae (Ludwignia peruviana); that had higher rates of translocation of heavy metals.